Isolation and phylogenetic relationship of orchid-mycorrhiza from Spathoglottis plicata of Papua using mitochondrial ribosomal large subunit (mt-Ls) DNA - SUPENI SUFAATI; VERENA AGUSTINI; SUHARNO SUHARNO (Society for Indonesian Biodiversity, 2012)
Sufaati S, Agustini V, Suharno. 2012. Isolation and phylogenetic relationship of orchid-mycorrhiza from Spathoglottis plicata of Papua using mitochondrial ribosomal large subunit (mt-Ls) DNA. Biodiversitas 13: 59-64. All terrestrial mycorrhiza have mutual symbiotic with mycorrhizal fungi in order to gain nutrient from surrounding environment. This study was done to isolate and to identify mycorrhiza orchid that associates with Spathoglottis plicata and were collected from Cagar Alam Pegunungan Cycloops (CAPC), Jayapura. Isolation of mycorrhizal orchid came after the modified method of Manoch and Lohsomboon (1992). The result showed that based on the morphological characteristic, there were presumably 14 isolations. However, only 2 isolations have been known, namely Rhizoctonia sp. and Tulasnella sp., while the rest were not identified yet. Among them, the DNA of the 11 isolations were able to beextracted for further analysis. The constructed phylogenetic tree performed that those species could be grouped into 4 major clusters. Two species, Rhizoctonia sp. and Tulasnella sp. were in different clusters.